1991
DOI: 10.1055/s-2007-1002589
|View full text |Cite
|
Sign up to set email alerts
|

Fibrinolytic Therapy of Deep Vein Thrombosis with Continuous Intravenous Infusion of a Recombinant Tissue Plasminogen Activator

Abstract: Recombinant human rt-PA was administered to 22 patients with deep vein thrombosis at a dosage of 30 to 120 mg/day (0.5 to 1.76 mg/kg body weight/24 hr) over 2 to 10 days. rt-PA induced phlebographically documented substantial recanalization in 18 of 21 patients. The lowest dose of 0.5 mg/kg/24 hr tested here was thrombolytically effective, whereas a dose of 0.95 mg/kg/24 hours and more led to hemorrhagic complications and premature discontinuation of therapy in four of six patients. Blood clotting analysis did… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1992
1992
2000
2000

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…The fibrin selectivity of this agent, compared to urokinase and streptokinase, suggests that its use might improve the risk-benefit ratio of thrombolytic therapy for DVL However, preliminary studies with the single-chain form of rt-PA, alteplase, (7)(8)(9) showed that short-duration (4-8 h) high dose (50-100 -g) infusions of this agent over 14. days yielded only limited success in terms of phlebographic rec analization and were associated with a risk of major bleeding of 30% (7).In a limited series of 7 patients, Zimmermann et al reported promising results with continuous infusions of 0.71 to 1.76 mdkglz4h for 2-4 days (10) and also observed a marked thrombolytic effect following 0.5 mglkglza h for 2-8 days (11).…”
Section: 23)mentioning
confidence: 99%
See 1 more Smart Citation
“…The fibrin selectivity of this agent, compared to urokinase and streptokinase, suggests that its use might improve the risk-benefit ratio of thrombolytic therapy for DVL However, preliminary studies with the single-chain form of rt-PA, alteplase, (7)(8)(9) showed that short-duration (4-8 h) high dose (50-100 -g) infusions of this agent over 14. days yielded only limited success in terms of phlebographic rec analization and were associated with a risk of major bleeding of 30% (7).In a limited series of 7 patients, Zimmermann et al reported promising results with continuous infusions of 0.71 to 1.76 mdkglz4h for 2-4 days (10) and also observed a marked thrombolytic effect following 0.5 mglkglza h for 2-8 days (11).…”
Section: 23)mentioning
confidence: 99%
“…The individual values of the Marder's venographic scores in the two groups are displayed in Fig. 1-. Thrombolysis was associated with improvements of the scores which decreased on average (median, range) from L8 units (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25) to 13 units in Group I (median decrease 3.0 units, n -1-5, p _ 0.32) and from 17.5 units (3-33) to 15.5 units (0-27) in Group II (median decrease 4.0 units, n _ 16, p _ 0.23). All paired venograms except three (one in Group I and two in Group II) were considered as being suitable for comparative qualitative assessment.…”
Section: Tieatment Protocolmentioning
confidence: 99%
“…When considering this therapy for a patient, the benefits and risks of this procedure must be weighed diligently (1)(2)(3)(4)(5)(6)(7)(8)(9). Numerous at tempts have been suggested including new drugs such as rt-PA (10)(11)(12)(13)(14)(15)(16)(17), new techniques (lysis block-technique, hyperthermic fi brinolysis) and new application schedules (18)(19)(20)(21) to improve treatment results. As far as our own results are concerned, sys temic intermittent application of ultra-high-dose streptokinase (UHSK), introduced by Martin et al in 1985 (22)(23)(24)(25)(26) seems to be the most effective treatment protocol (27).…”
Section: Introductionmentioning
confidence: 99%